Photoexcitation in Solids: First‐Principles Quantum Simulations by Real‐Time TDDFT (Adv. Theory Simul. 8/2018). Issue 8 (6th August 2018) - Lian, Chao; Guan, Mengxue; Hu, Shiqi; Zhang, Jin; Meng, Sheng
Abstract : Real‐Time TDDFT Solid‐state materials can exhibit highly nonlinear electronic and optical behaviors under laser excitation. However, a unified theoretical framework has not been established to explain the underlying mechanisms. In article number1800055, Sheng Meng and co‐workers develop an efficient real‐time time‐dependent density functional theory (TDDFT) approach for accurate simulations of excited state dynamics in solids. The photoexcitation process of the generation of hot electron‐hole pairs under laser pulse illumination in a layered solid is shown schematically.